Second‐generation dopamine agonists and recollection impairments in Parkinson's disease. Issue 2 (2nd July 2013) - Shepherd, Thomas A.; Edelstyn, Nicola M. J.; Mayes, Andrew R.; Ellis, Simon J.
Abstract : A selective deficit in the recollection of episodic details is frequently reported in Parkinson's disease (PD). Previous explanations implicate dopamine dysregulation in prefrontal structures on which strategic memory processes rely. However, neuroimaging advancements suggest dopaminergic dysregulation of hippocampally dependent memory processes. Accordingly, dopamine agonists, which target D3 receptors in the hippocampus, may impair hippocampal functioning, causing a more pronounced recollection decline. Recognition memory (RM), familiarity, and recollection were examined in 21 patients with mild‐to‐moderate PD (Hoehn and Yahr mean: 2.67). Patients were subdivided into two subgroups according to dopamine agonist (pramipexole [PPX] or ropinirole [RPR]), and completed matched versions of an RM test in a medicated and unmedicated condition (termed ON and OFF, respectively). Ten demographically matched healthy volunteers (HVs) also completed both RM tasks in two separate sessions. The PD group (PPX and RPR subgroups combined) showed impairments in RM and recollection, but spared familiarity. When subdivided by dopamine agonist, the PPX subgroup's ON‐medication recollection performance was significantly lower than that of both the HVs and RPR subgroup. There was no evidence of decline in OFF‐medication recollection or familiarity in either the PPX or RPR subgroups. Recollection in both PD subgroups correlated positively with a composite measure of recall, but not prefrontally dependent measures of cognitive control. These findings suggest that mild‐to‐moderate PD patients may show relatively preserved recollection and familiarity, but that recollection is selectively disrupted by PPX, but not RPR and that this effect may depend on disrupted hippocampal function rather than impaired pre‐frontally dependent executive functions.